Unique equilibrium in contests with incomplete information - Christian Ewerhart; Federico Quartieri (University of Zurich, Department of Economics, 2013)
Szidarovszky and Okuguchi (Games and Economic Behavior, 1997) have provided useful conditions for the existence of a unique pure-strategy Nash equilibrium in rent-seeking games of complete information. In this paper, we generalize their results to contests with incomplete informa tion. Two assumptions are imposed on the information structure. First, the players’valuations of winning are assumed to be multiplicatively separable (which includes the polar cases of private values and pure common value). Second, it is assumed that a player is never certain to be the only one with a positive budget. It is also shown that, unless the budgets of all players are zero in all states, at least two players realize a positive expected net rent.
Keywords: D72; C72; 330; Contests; Equilibrium existence and uniqueness; Incomplete; information; Rent dissipation